Formation of a thin and continuous MOF membrane with 2-D MOF nanosheets as seeds via layer-by-layer growth. Issue 68 (7th August 2019) - Ma, Yingnan; Dong, Zhaopeng; You, Meng; Zhang, Yufeng; Feng, Xianshe; Ma, Xiaohua; Meng, Jianqiang
Abstract : A thin MOF film on a polymer support with 2-D MOF nanosheets as seeds via layer-by-layer seeding growth shows excellent gas molecular sieving performance. Abstract : Current MOF composite membranes usually suffer from unduly thick MOF layers and poor adhesion with the polymer substrate. We prepared a thin MOF film (440 nm) on a polymer support with 2-D MOF nanosheets as seeds via a layer-by-layer growth. These 2-D MOF seeds not only provided bonding between the MOF film and the polymer substrate but also facilitated the formation of a continuous and defect-free MOF membrane, which demonstrated excellent performance in gas separation.